Electronically tunable voltage-mode universal filter with single-input five-output using simple OTAs - Kumngern, Montree; Suwanjan, Peerawut; Dejhan, Kobchai (My University, 2013)
This article presents a new electronically tunable voltage-mode universal biquadratic filter with single-input five-output using simple operational transconductance amplifiers (OTAs) and grounded capacitors. The proposed configuration provides low-pass, band-pass, high-pass, band-stop and all-pass voltage responses at a high-impedance input terminal that enables easy cascading in voltage-mode. The natural frequency and the quality factor can be set orthogonally by adjusting the circuit components. The natural frequency can also be controlled electronically by adjusting the bias currents of the OTAs. For realising all the five standard filtering functions, no critical-matching conditions are imposed and all the incremental parameter sensitivities are low. Experimental and simulation results that confirm the theoretical predictions are given. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: operational transconductance amplifier; single-input multiple-output filter; universal filter; voltage-mode circuit